Psychological Support to the Community During the COVID-19 Pandemic: Field Experience in Reggio Emilia, Northern Italy - Ghiretti, Fiorello; Gildoni, Gabriela; Grassi, Gaddo Maria; Torricelli, Laura; Benassi, Elena; Bonaretti, Elisa; Bonazzi, Francesca; Borelli, Sara; Cagnolati, Francesca; Covati, Katia; Errera, Francesca; Finardi, Vanessa; et al. (Frontiers in Psychology, 2020)
We report the field experience of the psychological staff of AUSL-IRCCS of Reggio Emilia, a local health system conglomerate serving half-million inhabitants catchment area in Emilia Romagna Region of Italy, during the coronavirus (COVID-19) pandemic. We provided a free phone-call psychological support for the community, with the specific aim of reducing stress caused by COVID-19 pandemic and its consequences, as quarantine and lock-down. We describe how the community used this opportunity of support in terms of problems reported and interventions provided. Our field experience suggests that a service of phone psychological support is feasible and quickly implementable in case of sudden emergencies that hit at different levels the whole community